Online or Blended Learning: Any Differences in Chemistry Learning Outcomes? - Toyib Febri Kisdiono; U.S. Supardi (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The world of education continues to evolve with changes in time and circumstances. Currently, the education sector faces a challenge due to the Covid-19 pandemic, which has resulted in a shift towards distance learning and online education. With the improvement in the situation, limited in-person learning has been resumed with blended learning. This shift in learning methods and models may impact student learning outcomes. The study aimed to investigate the difference in learning outcomes between online and blended learning, as well as identify any obstacles encountered. A survey-based ex post facto method was used for the study. The population consisted of 43 tenth-grade students (from the Social Science department of State Senior High School 1 Panggarangan) were selected using simple random sampling. Data was collected through documentation and interviews. A nonparametric Wilcoxon test was used for data analysis, and interview results were analyzed descriptively. The results of the Wilcoxon test showed a significant difference in learning outcomes (sig 0.000, p<0.05) between online and blended learning, with the latter producing better results. Network constraints, difficulty in comprehending material, excessive assignments, and lack of parental support were identified as obstacles in online learning. The study highlights that online learning may not be appropriate for high school students, particularly in schools facing internet access constraints and low motivation.